Ru(II) coordination compounds of NN bidentate chelators with 1, 2, 3 triazole and isoquinoline subunits: Synthesis, spectroscopy and antimicrobial properties. (1st February 2020) - Kreofsky, Nicholas W.; Dillenburg, Maxwell D.; Villa, Eric M.; Fletcher, James T.
Graphical abstract: Isoquinoline-containing bidentate chelators with varying 1- and 3-connectivity prepared from tandem CuAAC methods are capable of forming stable 3:1 Ru(II) coordination compounds. Isoquinoline connectivity influences the spectroscopic properties of these complexes, while isoquinoline incorporation can significantly improve antibacterial properties relative to analogous complexes with pyridine-containing chelators. Abstract: Bidentate chelators 1-(1-benzyl-1, 2, 3-triazol-4-yl)isoquinoline and 3-(1-benzyl-1, 2, 3-triazol-4-yl)isoquinoline were prepared from benzyl bromide and trimethylsilylethynylisoquinoline precursors using a tandem deprotection/substitution/CuAAC synthetic approach. Each chelator is capable of forming a stable 3:1 Ru(II) coordination compound, which forms as a geometric isomer mixture. These Ru(II) complexes possess unique MLCT absorbance signatures at 450/472 nm (1-isomer) and 367 nm (3-isomer) relative to their constituent chelating units. Minimum inhibitory concentration values as low as 0.4 μM are observed for Ru(II) complexes against representative Gram-positive bacteria Bacillus subtilis and Staphylococcus epidermidis . Comparing the MIC values of these isoquinoline compounds with analogous 2-(1-benzyl-1, 2, 3-triazol-4-yl)pyridine compounds shows a 2.5- to 40-fold improvement in potency. This study establishes that increased hydrophobicity introduced at the central chelating units of Ru(II) coordination compounds can be a useful means by which to optimize antimicrobial activity that is complimentary to the variation of peripheral substituent identity at the chelator's N1 triazole position.